Gut Helicobacter presentation by multiple dendritic cell subsets enables context-specific regulatory T cell generation - Russler-Germain, Emilie V (eLife, 2021)
Generation of tolerogenic peripheral regulatory T (pTreg) cells is commonly thought to involve CD103(+) gut dendritic cells (DCs), yet their role in commensal-reactive pTreg development is unclear. Using two Helicobacter-specific T cell receptor (TCR) transgenic mouse lines, we found that both CD103(+) and CD103(–) migratory, but not resident, DCs from the colon-draining mesenteric lymph node presented Helicobacter antigens to T cells ex vivo. Loss of most CD103(+) migratory DCs in vivo using murine genetic models did not affect the frequency of Helicobacter-specific pTreg cell generation or induce compensatory tolerogenic changes in the remaining CD103(–) DCs. By contrast, activation in a Th1-promoting niche in vivo blocked Helicobacter-specific pTreg generation. Thus, these data suggest a model where DC-mediated effector T cell differentiation is ‘dominant’, necessitating that all DC subsets presenting antigen are permissive for pTreg cell induction to maintain gut tolerance.